Study of the Influence of Online Games on Adolescent Psychology in Parungponteng District: Analysis of Intensity of Use, Type of Game, and Psychological Impact - Astrid Sulistya Azahra; Jumadil Saputra; Kalfin Kalfin (Research Collaboration Community (RCC), 2024)
This research aims to examine the influence of online games on adolescent psychology in Parungponteng District. By collecting data from 30 respondents through questionnaires, this research analyzed the intensity of game use, the types of games played, and the psychological impact of online game addiction on teenagers. The research results show that teenagers tend to spend an average of 15 hours per week playing online games, with the majority choosing Role-Playing Games (RPG) and Multiplayer Online Battle Arena (MOBA) games. The psychological impacts of online gaming addiction include a lack of interest in other activities and feelings of anxiety when unable to play. The implications of this research include educational awareness of game use, development of educational games, the active role of parents and educators, as well as the development of time management skills.